PENGARUH PENDIDIKAN DALAM KELUARGA TERHADAP PRESTASI BELAJAR SISWA - Ananda, Dhiva Raysha; Ayub, Daeng; Muryanti, Muryanti (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
This study aims: 1) to determine the level of education in families at SDIT Raudhaturrahmah, Marpoyan Damai District, Pekanbaru City. 2) to determine the level of learning achievement of students at SDIT Raudhaturrahmah, Marpoyan Damai District, Pekanbaru City. 3) to determine the influence of education in families on the learning achievement of students at SDIT Raudhaturrahmah, Marpoyan Damai District, Pekanbaru City. This type of research is ex-post facto with a quantitative approach. The population in this study were all students at SDIT Raudhaturrahmah, Marpoyan Damai District, Pekanbaru City. The sampling technique used Simple Random Sampling, which is a sampling method that gives each member of the population an equal opportunity to be selected. Based on the Slovin formula with an error rate of 5%, a sample of 99 students at SDIT Raudhaturrahmah, Marpoyan Damai District, Pekanbaru City was obtained. The research instrument used a family education questionnaire compiled based on the following indicators: provision of learning time and facilities, emotional support, provision of knowledge and information, supervision and guidance, and motivation and encouragement. The results of the inferential analysis showed a positive and significant influence between family education on student achievement at SDIT Raudhaturrahmah, Marpoyan Damai District, Pekanbaru City, with a large influence of 14.7%, which is included in the low interpretation.